Essays on Economics, Disability and Employment. Ensayos sobre Economía, Discapacidad y Empleo, P. Alonso González, D. Cantarero Prieto, J.J. Núñez Velázquez, M. Pascual Sáez (Eds.). Delta Publicaciones, Madrid (2009). - Cruz-Morato, Marco Antonio (Elsevier Masson, 2010)
The negative situation of disabled people used to be an issue traditionally neglected by economic science. However, there does seem to be an economic factor in the satisfaction of these people’s needs. An economic approach might therefore be useful to analyze this matter, in order to improve the welfare of disabled people by improving the allocation of resources. The labour situation of this group, quantitatively and qualitatively worse than the non-disabled people one, seems to be the main problem; with low employment rates and being more prone to inactivity.
Keywords: Minusvalidos; Empleo; Disability